Ustrój prawny izb gospodarczych a lobbing - Wykrętowicz, Stanisław (The legal system of chambers of commerce and lobbing, 2005)
Chambers of commerce are some of the oldest institutions of entrepreneurs’ activity. The article presents their origins and evolution of their legal systems: from private corporate systems as voluntary associations to public corporate systems that evolved later into self-governing economic institutions independent from governments, assuming a form of decentralized public administration. Only the self-governing chambers of commerce (the French model) exert direct influence on the market, while chambers that function as voluntary associations of entrepreneurs (the Anglo-Saxon model) deform that order through their lobbing in (he name of their private interests. Upon this historical and theoretical development in the background, the article discusses the shaping of chambers of commerce in the Republic of Poland II, the unsuccessful restitution of such chambers in the Republic of Poland III and the negative consequences which disturb the market order in Poland today.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1090, s. 26-41